2008
DOI: 10.1083/jcb.200801145
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule cross-linking triggers the directional motility of kinesin-5

Abstract: Although assembly of the mitotic spindle is known to be a precisely controlled process, regulation of the key motor proteins involved remains poorly understood. In eukaryotes, homotetrameric kinesin-5 motors are required for bipolar spindle formation. Eg5, the vertebrate kinesin-5, has two modes of motion: an adenosine triphosphate (ATP)–dependent directional mode and a diffusive mode that does not require ATP hydrolysis. We use single-molecule experiments to examine how the switching between these modes is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
160
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(181 citation statements)
references
References 29 publications
18
160
1
1
Order By: Relevance
“…Whereas processive motors take hundreds of steps before they detach from a track, nonprocessive motors detach after a single step. Some motors such as kinesin-5, kinesin-14, and cytoplasmic dynein exhibit low or variable processivity depending on the local environment, including modified microtubule (MT) lattice and the arrangement of MT tracks (6)(7)(8)(9). All types of motors have been shown to increase the force or run length of cargos, which are generally larger than can be achieved by single motors (10)(11)(12), and many studies have suggested that the number of motors in these teams regulates the transport (3,5,10).…”
mentioning
confidence: 99%
“…Whereas processive motors take hundreds of steps before they detach from a track, nonprocessive motors detach after a single step. Some motors such as kinesin-5, kinesin-14, and cytoplasmic dynein exhibit low or variable processivity depending on the local environment, including modified microtubule (MT) lattice and the arrangement of MT tracks (6)(7)(8)(9). All types of motors have been shown to increase the force or run length of cargos, which are generally larger than can be achieved by single motors (10)(11)(12), and many studies have suggested that the number of motors in these teams regulates the transport (3,5,10).…”
mentioning
confidence: 99%
“…Positively charged coverslips with DETA were prepared according to ref. 32. Flow chambers were assembled by joining a DETA-treated coverslip and a nontreated coverslip using double stick tape.…”
Section: Methodsmentioning
confidence: 99%
“…The screen yielded a compound which inhibited Eg5, a member of the kinesin-5 family of motor proteins. Eg5, also known as kinesin spindle protein (KSP), is a plus-end directed motor which acts as a homotetramer to cross-link and slide anti-parallel microtubules at the onset of mitosis, thereby pushing apart the centrosomes to form the bipolar spindle [12]. In the absence of Eg5 function, the centrosomes remain tightly clustered yielding a monopolar spindle; consequently, the inhibitor was christened Monastrol [11].…”
Section: Ksp Inhibitors-bringing the Antimitotic Concept Into The 21smentioning
confidence: 99%